Experience of patients with chronic conditions with telemedicine in primary care - Prevodnik, Katja (Obzornik zdravstvene nege, 2022)
Introduction: Telemedicine is becoming an increasingly important strategy for the management of chronic diseases, which cause a high proportion of deaths in Slovenia. The aim of this study was to investigate user experiences related to the use of telemedicine devices and experiences with telemedicine among patients diagnosed with chronic diseases in primary care. Methods: We conducted four focus groups with 19 patients with type 2 diabetes and/or hypertension in July 2020 in a Slovenian primary health care centre. Transcripts were analysed according to the principles of inductive thematic analysis. Results: Using inductive thematic analysis, seven themes were identified: advantages and disadvantages of telemedicine, ease of use of telemedicine, two-way communication with health professionals, impact of telemedicine on patients' health, desire to use telemedicine and its accessibility, influence and support from the environment, and concern for own health. The themes are composed of 10 subthemes and 29 factors. Discussion and conclusion: Regular use of telemedicine is most strongly influenced by patients' perceived need to use it and instructions from health professionals. Despite patients' positive experiences of using telemedicine devices, an individual assessment of their suitability for each patient is needed, including an assessment of the patient's health status, attitude towards health, and level of digital literacy.
Keywords: diabetes; Družinska medicina; Fokusne skupine; hipertenzija; hypertension; Kronični bolniki; kvalitativna raziskava; primarno zdravstveno varstvo; primary health care; qualitative study; Telemedicina; telemedicine; uporabniška izkušnja; user experience